Editorial - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
This JIFAM, Volume 5, Issue 1, April 2023 publishes 5 papers related to the road construction as asset infrastructures to develop the sustainable asset management for infrastructures. The JIFAM Editorial Team express their gratitude to the authors who already submitted their papers for the fifth volume (issue 1, April 2023).